2010
DOI: 10.1111/j.1365-2427.2009.02281.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing pollution of toxic sediment in streams using bio‐ecological traits of benthic macroinvertebrates

Abstract: 1. We examined the accuracy of a multimetric approach based on 22 biological and ecological traits of benthic macroinvertebrate communities to assess toxic sediment pollution in streams. 2. Faunal and chemical data from sites located on 150 medium-sized mountain streams in France were analysed. We used 18 additional sites, not included in the multimetric tool development as a test data set. A toxic quality class (from 'high' to 'poor ⁄ bad') was preassigned to each site using the French water quality assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 68 publications
0
51
1
Order By: Relevance
“…Moreover, active bioturbators can hence promote release of sediment-associated contaminants across the benthic-pelagic ecosystem boundary, thereby stimulating delivery of contaminants from what is often the most polluted environmental compartment in freshwater ecosystems (Burton, 2013;Roig et al, 2015). Although research linking traits to toxicant sensitivity is still relatively rare, trait based ecotoxicology offers a possibly potent tool for predicting sensitivity of benthic invertebrates and the benthic community to sediment-associated contaminants (Baird et al, 2008;Archaimbault et al, 2010). It is alarming though, that the paucity of sediment toxicity data still poses the largest obstacle to deriving reliable SQGs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, active bioturbators can hence promote release of sediment-associated contaminants across the benthic-pelagic ecosystem boundary, thereby stimulating delivery of contaminants from what is often the most polluted environmental compartment in freshwater ecosystems (Burton, 2013;Roig et al, 2015). Although research linking traits to toxicant sensitivity is still relatively rare, trait based ecotoxicology offers a possibly potent tool for predicting sensitivity of benthic invertebrates and the benthic community to sediment-associated contaminants (Baird et al, 2008;Archaimbault et al, 2010). It is alarming though, that the paucity of sediment toxicity data still poses the largest obstacle to deriving reliable SQGs.…”
Section: Resultsmentioning
confidence: 99%
“…The resistance and the resilience characteristics adopted by taxa therefore determine the response of the community to disturbance events. The advantage of using functional traits instead of taxonomic composition of communities is bound to the a priori predictable response of traits to individual stressors [16,54,77]. Each trait is supposed to respond independently to a given pressure and each pressure affects different traits.…”
Section: Community Functioning: Species Traitsmentioning
confidence: 99%
“…At present, fuzzy coding analysis has been successfully used to match species with individual traits [16,77], but other approaches may be more powerful {e.g., Giller et al [51] suggested the allocation of species into groups based on several relevant traits}.…”
Section: Future Research Directionsmentioning
confidence: 99%
See 2 more Smart Citations